Positive assessment of a legal entity’s activities as a personal non-property benefit - Ратушна, Богдана; Ratushna, Bohdana (Видавництво Львівської політехніки, 2024)
У статті досліджено поняття “ділова репутація” юридичних осіб як учасників суспільних відносин. Встановлено, що низка особистих немайнових прав юридичних осіб, серед яких і право на недоторканність ділової репутації юридичних осіб, передбачена статтею 94 Цивільного кодексу України. Виявлено, що ділова репутація є особистим немайновим благом юридичних осіб. Водночас у Цивільному кодексі України відсутнє визначення поняття “ділова репутація” юридичних осіб, що зумовлює необхідність викласти таке визначення та запропонувати законодавчо закріпити його у Цивільному кодексі України. Встановлено, що наукова асоціація України не оминула увагою це питання і запропонувала декілька варіантів визначення поняття “ділова репутація” юридичних осіб. Верховний Суд України в постанові Пленуму ВСУ від 27.02.2009 р. № 1 також виклав власне визначення цього поняття, згідно з яким ділова репутація – це оцінка підприємницької, громадської, професійної чи іншої діяльності юридичних осіб, яка здійснюється такими особами як учасниками суспільних відносин. На підставі цього визначення запропоновано удосконалений варіант поняття “ділова репутація”, а саме: “позитивна оцінка підприємницької, громадської, професійної чи іншої діяльності юридичних осіб, що здійснюється такими особами як учасниками громадськості”. Саме таке визначення поняття ділової репутації запропоновано закріпити в Цивільному кодексі України. Доведено, що негативна оцінка діяльності юридичних осіб свідчить про відсутність у таких юридичних осіб ділової репутації. Також встановлено, що ділова репутація є презумпцією закону, яка поширюється на кожну юридичну особу. Як і будь-яку іншу презумпцію закону, наявність у юридичної особи ділової репутації можна спростувати в судовому порядку, надавши негативну оцінку діяльності такої юридичної особи.

In the article research of concept “business reputation” is carried out legal entities as participants of public relations. It is set that the row of the personal unproperty rights for legal entities, among that and right on inviolability of business reputation of legal entities, is envisaged in the article 94 of the Civil code of Ukraine. It is educed that business reputation is the personal unproperty blessing of legal entities. At the same time in the Civil code of Ukraine absent determination of concept “business reputation” legal entities, that causes a necessity to set forth such determination and offer him legislatively to fasten in the Civil code of Ukraine. It is set that the scientific association of Ukraine did not go round attention this question and offered a few variants of determination of concept “business reputation” legal entities. Supreme court of Ukraine in resolution of Plenum ВСУ from 27.02.2009 No. 1 also set forth own determination of this concept, in accordance with that business reputation is an estimation of entrepreneurial, public, professional or other activity of legal entities, that is carried out by such persons as participants of public relations. On the basis of this determination the improved variant of concept “business reputation” is offered, namely: “positive estimation of entrepreneurial, public, professional or other activity of legal entities, that is carried out by such persons as participants of public. Just the same determination of concept of business reputation it is suggested to fasten in the Civil code of Ukraine. It is well-proven that the negative estimation of activity of legal entities testifies to absence of business reputation for such legal entities. It is also set that business reputation is presumption of law, that is assumed after every legal entity. As well as any other presumption of law, a presence for the legal entity of business reputation can be refuted in the judicial order by establishment of negative estimation of activity of such legal entity.
Позитивна оцінка діяльності юридичної особи як особистої немайнової вигоди
Keywords: юридична особа; особисті немайнові права; ділова репутація; Цивільний кодекс України; legal entity; personal unproperty rights; business reputation; Civil code of Ukraine; 342